Immunotherapy in gliomas: Are we reckoning without the innate immunity?. (April 2019) - Vismara, Marco Flavio Michele; Donato, Annalidia; Malara, Natalia; Presta, Ivan; Donato, Giuseppe
Innate immunity plays a central role in neoplasms, including those affecting the central nervous system (CNS). Nowadays, tumors classification, especially that regarding gliomas, is based on molecular features such as mutations in isocitrate dehydrogenase (IDH) genes and the presence of co-deletion 1p/19q. Therapy, in most cases, is based on surgery, radiotherapy, and pharmacological treatment with chemotherapeutic agents such as temozolomide. However, the results of the treatments, after many decades, are not completely satisfactory. There is a class of drugs, used to treat cancer, which modulates immune response; in this class, the immune checkpoint inhibitors and vaccines play a prominent role. These drugs were evaluated for the treatment of gliomas, but they exhibited a poor outcome in clinical trials. Those scarce results could be due to the response of tumor-associated macrophage that creates imbalances between innate and adaptive immunity and changes in blood–brain barrier properties. Here, we have briefly reviewed the current literature on this topic, focusing on the possible role for innate immunity in the failure of immunotherapies against brain tumors.